How to do biography : a primer - Hamilton, Nigel (Cambridge : Harvard University Press, 2008)
Following his recent Biography: A Brief History (from Harvard), award-winning biographer and teacher Nigel Hamilton tackles the practicalities of doing biography in the first succinct primer to elucidate the tools of the biographer's craft.
The task of biography -- What is your agenda? -- Defining your audience -- Researching your subject -- The shape of a life -- The starting point -- Birthing your subject -- Childhood and youth -- Love stories -- Life's work -- The twilight years -- Ending your story -- Autobiography and memoirs -- Memoir -- Truth--and its consequences -- The afterlife.
Includes bibliographical references (pages 362-367) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Biography as a literary form; Biography -- Research -- Methodology; Autobiography -- Authorship; Biography; Biographie (Genre littéraire); Biographies -- Recherche -- Méthodologie.; Biographies; biographies (literary genre); biography (general genre); LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; Autobiography -- Authorship; Biography as a literary form; Biography -- Research -- Methodology